CD4 count and oral health related quality of life of HIV-infected individuals at a tertiary healthcare center in Dharan – A cross-sectional study - Shrestha, Ashish; Rimal, Jyotsna; Poudyal, Nimesh (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objective: Patients with severe immuno-suppression are at risk of having poor oral hygiene and severe periodontal diseases, thus limiting their quality of life. The objective of this study was to assess the impact of oral health-related quality of life (OHRQoL) in patients with HIV/AIDS and its association with the CD4 cell count. Materials & Methods: A cross-sectional study was conducted using Oral Health Impact Profile-14 (OHIP-14) among 122 HIV/AIDS patients visiting the CD4 laboratory at a tertiary healthcare center at Dharan, from January-December 2009. Oral examination and recording of dental indices were done. CD4 cell count was correlated with OHIP-14 and dental indices using Spearman’s rho; p < 0.01 was considered as statistically significant. Results: Sixty four males and 58 females with median age of 34 years had a mean CD4 cell count of 360.46 cells/mm3 (range=111-1076 cells/mm3). OHRQoL was affected in 25.4% of the individuals with mean OHIP-14 score of 2.5. Most of the individuals (85.7%) were on ART, never used tobacco (68%) or alcohol (74.5%). Mean OHI-S and DMFT were 1.65 and 1.57, respectively and periodontal pocket observed in only 3.3% individuals. The CD4 cell count had no significant positive correlation with OHIP-14 ((rs=0.071; p=0.61), OHI-S (rs=0.21; p=0.127) and DMFT (rs=0.015; p=0.912). There was no significant difference in parameters with regards to gender. Conclusion: Although CD4 cells are an important indicator for clinical aggravation of HIV infection, OHRQoL and oral health as measured by OHI-S, DMFT and CPI are not directly associated to the CD4 cell count.